Investigating the indeterminacy of the divine nature without determination from the perspective of Islamic mysticism - Ahmad Saeidi (حکمت اسرا)
Almost all prominent Muslim thinkers consider both the theory of "Tashbih" ("similarity and embodiment") and the theory of "Taatil" ("the impossibility of knowing God") to be invalid and they believe that despite the fact that God is superior from the attributes of creatures, his brief and non-exhaustive knowledge is possible to achieve. The mystics also consider "Tashbih" and "Taatil" to be invalid, and they consider it possible to know God briefly, but they, unlike other Muslim thinkers, believe that no creature can see and describe the essence of God without a determination.According to him, what is thought to be a brief knowledge and description of the divine essence according to the essence, in fact, it is a brief knowledge and description of the essence according to the determinations and according to the determinations. This point of view can neither be considered as "Tashbih" nor as "Taatil". The view of the mystics regarding the knowledge of the essence of the essence is "super-composition and analogy of the essence".In the present article, we have analyzed and explained the indeterminacy of essence with a clear analytical-descriptive method and highlighted some similarities and differences with the thought of philosophers and the theory of "Taatil" and mentioned some mystical and narrative evidences.